Nationwide Bibliometric Analysis of Integrated Plastic Surgery Program Directors. Issue 1 (10th January 2023) - Seu, Michelle Y.; Esmaeeli, Shooka; Wiegmann, Aaron L.; Akin, Jennifer; Jaraczewski, Taylor; Dadrass, Farnaz; Xu, Thomas Q.; Dorafshar, Amir H.; Shenaq, Deana
Abstract : Background: Studies have linked bibliometric indices with the academic level of plastic surgeons, but this relationship has not been explored with residency program directors (PDs). As teachers of the next generation, PDs' academic performance is an important component of residency program success. We sought to identify distinguishing characteristics of integrated plastic surgery programs, focusing on their PD bibliometric indices. Methods: We identified plastic surgery programs based on 2021 Doximity reputation and research output rankings, respectively, and then divided them into four quartiles (Q1–Q4). PD academic history and bibliometric indices (h-index, the number of publications, and citations) were collected through Doximity profiles and program websites: PubMed, Scopus, Google Scholar, American Society of Plastic Surgeons, and Accreditation Council for Graduate Medical Education. Results: Eighty-four programs were identified. There was a significant positive relationship between h-index, the number of publications, and type of research with reputation ranking ( P < 0.05). After adjusting for years of experience post-training, h-index (OR = 1.24; P < 0.001) and the number of publications (OR = 1.05, P < 0.001) were significantly associated with reputation ranking. There was a statistically significant relationship between PD research fellowship completion and research output ranking ( P < 0.01). After adjusting for years of experience post-training, h-index (OR = 1.05; P = 0.047) and the number of publications (OR = 1.01; P = 0.04) were significantly associated with research output ranking. Conclusion: Higher ranked programs tend to have PDs who have a strong record of scholarly activity, as evidenced by certain bibliometric indices.